Elaboração de um instrumento de classificação da empatia clínica demonstrada pelos estudantes de medicina - Teixeira, Cleuza Guimarães (2023)
Introduction: Empathy is the ability to put oneself in another's place, understand and respond appropriately to the emotions of others. In the clinical context, empathy is related to improved diagnosis and adherence to proposed treatments, and greater patient satisfaction. Apparent empathy can present itself at different stages development. Objective: To develop an instrument that allows the classification of clinical empathy demonstrated by medical students when using the Health Empathy Map (HEM). Methodology: This is a study with a mixed (qualitative and quantitative) and descriptive approach, developed in three stages. (1) Initially, an empathy categorization model was proposed, which served as the basis for the development of the clinical empathy classification instrument (CECI-HEM). (2) Then, the validations of construct, content, criterion and precision of the elaborated instrument were performed. (3) Finally, an analysis of the clinical empathy demonstrated by the students was carried out. The model was evaluated by specialists in the subject and professors of clinical practice. To determine the level of agreement between the evaluating professors in regards to the classification of the student's empathy in the proposed categories, the Fleiss Kappa index (p < 0.05) and the Gwet AC1 statistic were used when there was a significant imbalance and descriptive analysis of the resulting data. Results: The results showed that the instrument was able to address the dimensions of clinical empathy, proved to be easy to understand and made it possible to identify the student's empathy category. It presented a reasonable agreement (0.20 to 0.40) in the 2nd quadrant for the affective dimension and final dimensionality, and in the 4th quadrant for the social dimension and final dimensionality. There was moderate agreement (0.40 to 0.60) in the 2nd quadrant for the biomedical and social dimensions, in the 3rd quadrant that assesses primary empathy, and in the 4th quadrant for the affective dimension. Lastly, there was a strong or almost perfect agreement (> 0.60) in the 1st quadrant that evaluates the extended empathy and in the 4th quadrant for the biomedical dimension. Final considerations: The CECI-HEM makes it possible to identify the classification of clinical empathy demonstrated by the student, and was considered, by the participants of the study, a useful tool to assist in teaching and developing empathy in the learning environment of clinical practice.